PERFORMANCE OF OPTIMIZED ROUTING IN BIOMEDICAL WIRELESS SENSOR NETWORKS USING EVOLUTIONARY ALGORITHMS - Anand, Jose; Jeevaratinam, Raja Paul Perinbam; Deivasigamani, Meganathan (Comptes rendus de l'Academie bulgare des Sciences, 2015)
Biomedical Wireless Sensor Network (BWSN) is used to convey the physiological parameters of a patient in any abnormal condition to the healthcare personnel in real-time. For conveying the information from the patient's body to the remote healthcare office the BWSN should choose an optimized path for communication to increase the life time of the nodes. This paper compares the performance of Genetic Algorithm (GA) based routing and Particle Swarm Optimization (PSO) based routing to route the sensed physiological parameters if required from the individual node to the remote health care station. Simulation studies were carried out using NS 2 with a set of 100 mobile biomedical wireless sensor nodes in an area of 1000 x 1000 m flat space operating for 600 s. Simulation results demonstrate that PSO-based routing gives better results than GA-based routing. This is because in GA-based routing the local extremum is reached with little probability due to its good resolution and its usage for reaching the vicinity of the global extremum.Key words: biomedical wireless sensor network, genetic algorithm, particle swarm optimization, optimization, routing